The Uniqueness of Islamic Journalism at the Indonesian Islamic Universities in the Digital Age - Musyafak, Najahan; Hilmi, Mustofa; Fabriar, Silvia Riskha (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Islamic journalism has been intensely discussed among Islamic Universities in Indonesia. This study at least can be identified into three models. First, is the study of Islamic journalism as an activity that informs issues, events and phenomena related to Islamic values. Second, is the study of Islamic journalism as an Islamic way and method of journalistic activities. Third, the study of journalism as Islamic principles is the basis for journalistic activities. This study aims to complement the previous studies that gave few concerns to a comprehensive understanding of Islamic journalism, particularly the different concept with journalism studies. This study relies on primary and secondary data using a qualitative descriptive approach. Primary data was taken from Focus Group Discussion (FGD) by inviting 6 heads of the Islamic Journalism Study Program of Islamic Universities, lecturers, practitioners of journalistic and media, alumni, and communication students. At the same time, the secondary data was taken from the academic curriculum of several journalistic programs across the archipelago, namely UIN Walisongo Semarang, UNPAD Bandung, UGM Yogyakarta, UNDIP Semarang, UNAIR Surabaya, UI Jakarta, and other online sources. This study found that each university has uniqueness in formulating its curriculum, especially in integrating the concepts of Journalism and Islam.